Tinjauan Maqashid Al-Syariah terhadap Kepastian Hukum Pencatatan Perkawinan di KUA Kecamatan Bengalon - Rani, Elisa; Musthato’, Musthato’; Prima, Anggra (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the legal certainty of marriage registration from the perspective of Maqashid al-Syariah, with a case study at the Office of Religious Affairs (KUA) in Bengalon District. Although marriage registration is not a pillar or requirement for the validity of a marriage in Islamic law, it plays a crucial role in ensuring legal certainty, protecting the rights of spouses and children, and preventing future disputes. The research employs a descriptive qualitative method with data collected through observation, interviews with the head of the KUA and marriage registration officers, and documentation from relevant sources. This approach allows for an in-depth understanding of the marriage registration process in relation to the core objectives of Islamic law (al-Kulliyat al-Khams). The findings indicate that marriage registration supports legal certainty in accordance with the five main goals of Maqashid al-Syariah: protecting religion (hifz al-din) by ensuring compliance with Islamic and state legal norms; protecting life (hifz al-nafs) by safeguarding the rights of spouses and children; preserving lineage (hifz al-nasl) by securing the legal status and inheritance rights of children; preventing illegal or unrecognized marriages, which contributes to social order; and protecting wealth (hifz al-mal) by ensuring economic rights within marriage. Thus, marriage registration serves as a vital instrument in promoting public welfare.